Lipoprotein associated phospholipase A2 concentration predicts total and cardiovascular mortality independently of established risk factors (The Ludwigshafen risk and cardiovascular health study) - Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Grammer, Tanja B.; März, Winfried (Clinical laboratory, 2011)
Background: Lipoprotein-associated phospholipase A2 (LpPLA2) is a lipoprotein-bound enzyme involved in inflammation and atherosclerosis. This cohort study investigates LpPLA2 concentration to predict cardiovascular and total mortality in patients scheduled for coronary angiography. Methods: LpPLA2 concentration was determined in 2298 patients with and in 661 patients without angiographically confirmed coronary artery disease (CAD). During the median observation period of 8.0 years 686 patients died. Results: In patients with tertiles of LpPLA2 of 307 - 475 ng/mL, or ≥475 ng/mL unadjusted hazard ratios (HR) for total mortality were 1.47 (95 % CI 1.21 - 1.80; p <0.001), and 1.63 (95 % CI 1.35 - 1.97; p <0.001), respectively, compared to patients with LpPLA2 ≤307 ng/mL. HRs for cardiovascular death were 1.33 (95 % CI 1.04 - 1.71; p = 0.026), and 1.59 (95 % CI 1.26 - 2.02; p <0.001), respectively. After accounting for established risk factors and including angiographic CAD status and high sensitivity C-reactive protein (hsCRP), the 3rd tertile of LpPLA2 concentration predicted death from all causes with a HR of 1.40 (95 % CI 1.15 - 1.71; p = 0.001) and cardiovascular death with a HR of 1.35 (95 % CI 1.05 - 1.73; p = 0.018). LpPLA2 increased the risk of cardiovascular death significantly even in individuals with high hsCRP. In patients with hsCRP >3.3 mg/L and LpPLA2 >392 ng/mL the risk of cardiovascular death was almost two-fold higher compared to patients with low hsCRP and low LpPLA2 with a HR of 1.98 (95 % CI 1.50 - 2.62; p <0.001). Conclusions: LpPLA2 concentration predicts risk for total and cardiovascular mortality independently from established risk factors and indicates risk for cardiovascular death even in patients with high hsCRP levels.
Gesehen am 08.08.2022